Stunting and undernutrition among adolescent girls of indigenous communities in Telangana, India: A cross sectional study - Ravula, Padmaja; Kasala, Kavitha; Pramanik, Soumitra; Selvaraj, Aravazhi (International Crops Research Institute for the Semi-Arid Tropics, 2023)
Despite economic progress in recent decades, the indigenous population in India remain at risk of malnutrition due to major dependence on traditional agricultural practices, poverty, illiteracy and low personal and environmental hygiene. This study investigates the incidence, causes and socioeconomiccultural determinants of three indicators of chronic malnutrition—stunting, thinness and undernutrition— among adolescent girls from indigenous communities from selected sites in Telangana, India. The data on demographic and nutritional indicators using a mixed-methods approach was collected in 2017 from 695 adolescent girls out of 2,542 households. These adolescents were grouped into two categories—early adolescents (11–14 years ) and late adolescents (15– 18 years). The analysis showed that, overall, 13% of adolescent girls in the sample were of normal nutritional status and 87% were either stunted/underweight/ thin or a combination of two or three indicators. Girls in early adolescence showed a higher prevalence of being underweight (24.4%) whereas stunting was higher in late adolescent category (30%). The logistic regressions supported these findings and identified key factors influencing this result. Education of head of the household and the adolescent girl, and availability of toilet infrastructure by households played a significant role in reduction of malnutrition, especially in stunting and underweight categories. The sociocultural norms around food that starchy staples are the most important in the diet and early age of marriage were also found to be influencing the nutritional status. The study concludes the need for concerted policies, programs, nutrition education sessions and behavior change campaigns aimed at adolescent girls’ nutrition among the indigenous communities.